Susceptibility to autoimmune myocarditis is associated with intrinsic differences in CD4(+) T cells - Chen, P (Blackwell Science Inc, 2012)
A.SW and B10.S mice share the same major histocompatibility complex (MHC) haplotype (H-2(s)). However, A.SW mice are susceptible to experimental autoimmune myocarditis (EAM) and develop severe disease after immunization with myosin, whereas B10.S mice are resistant. We found that naive A.SW mice have intrinsically increased total CD4(+) T cell counts and increased proportions of CD4(+) T cells in their spleens compared to B10.S mice. Among total CD4(+) T cells, naive A.SW mice have a lower relative frequency of forkhead box protein 3 (FoxP3(+))CD25(+) regulatory T cells (T(regs)). A.SW mice also had a higher proportion of CD4(+) T cells and a lower proportion of T(regs) in their hearts and spleen during EAM, with greater T cell activation and proliferation, compared to B10.S mice. These differences in the T cell compartment were not antigen-specific, as ovalbumin/complete Freund's adjuvant (OVA/CFA) or CFA immunization elicited the same differences in CD4(+) T cells and T(regs) between A.SW and B10.S mice. Moreover, A.SW mice had more T helper type 17 (Th17) cells and B10.S had more Th1 cells in their hearts. The higher percentage of CD4(+) T cells and their enhanced potential to differentiate towards the Th17 pathway was also observed in naive A.SW mice. Interleukin (IL)-6 is required for Th17 induction. Interestingly, IL-6Rα expression was greater on naive A.SW CD4(+) T cells, compared to B10.S CD4(+) T cells, indicating that this intrinsic difference, together with a relatively lower T(reg) proportion of CD4(+) T cells, might lead to heightened Th17 responses and greater susceptibility to autoimmunity in A.SW mice.